2021
DOI: 10.3390/polym13183028
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Electrical and Thermal Properties for Magnetic Fe3O4-Coated SiC-Filled Epoxy Composites

Abstract: Orderly arranged Silicon carbide (SiC)/epoxy (EP) composites were fabricated. SiC was made magnetically responsive by decorating the surface with iron oxide (Fe3O4) nanoparticles. Three treatment methods, including without magnetization, pre-magnetization and curing magnetization, were used to prepare SiC/EP composites with different filler distributions. Compared with unmodified SiC, magnetic SiC with core-shell structure was conducive to improve the breakdown strength of SiC/EP composites and the maximum enh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…The conductivity range of TCAs is reported as 1-30 Wm −1 K −1 for sufficient heat transfer [44]. The thermal conductivity of epoxy has been increased using ceramic [45], metallic [46], and carbonbased [47] conductive fillers to increase the thermal conductivity of the epoxy, which are described below.…”
Section: Adhesives With Improved Conductivitymentioning
confidence: 99%
“…The conductivity range of TCAs is reported as 1-30 Wm −1 K −1 for sufficient heat transfer [44]. The thermal conductivity of epoxy has been increased using ceramic [45], metallic [46], and carbonbased [47] conductive fillers to increase the thermal conductivity of the epoxy, which are described below.…”
Section: Adhesives With Improved Conductivitymentioning
confidence: 99%
“…Among these alternatives, Fe 3 O 4 exhibits more promising characteristics as a filler. Nevertheless, the practical application of Fe 3 O 4 encounters certain limitations, including nanoparticle agglomeration, poor compatibility with organic matrix, and the possibility to form conductive pathways [ 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…To address these challenges, coating is regarded as an effective solution that enables better filler dispersion by introducing various functional layers and thus effectively modulating the dielectric properties of composite materials. Numerous studies have confirmed the effectiveness of coating techniques [ 22 , 30 , 31 , 32 , 33 ], such as the coating of silicon dioxide (SiO 2 ) on the surface of ultrafine barium titanate (BaTiO 3 ) nanoparticles [ 34 ] or the coating of Fe 3 O 4 with functionalized carbon layers and organic polyaniline (PANI) using high-temperature-resistant polymers [ 23 ]. Simultaneously, due to the limited operating temperature of commercial biaxially oriented polypropylene (BOPP) films, they fail to meet the requirements of high-temperature electrical systems [ 35 , 36 , 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…With the widespread application of advanced electronic devices, our lives are enhanced by ever greater convenience. However, the development of electronic devices has created considerable quantities of electromagnetic (EM) pollution due to electromagnetic radiation and EM interference; this pollution affects human health and the normal operation of other devices [ 1 , 2 , 3 , 4 , 5 , 6 ]. In order to avoid these issues, many novel materials with high EMI shielding performance were explored with the aim of addressing problems related to EMI and radiation [ 7 ].…”
Section: Introductionmentioning
confidence: 99%